Phytochemical, Proximate, and Vitamin C Content in Morinda citrifolia (Noni) - Selina Ama Saah; David Adu-Poku (Journal of Tropical Pharmacy and Chemistry, 2021)
Morinda citrifolia, L commonly called noni, has a long history as a medicinal plant and is reported to have a broad range of therapeutic effects, including antibacterial, antiviral, antifungal, antitumor, antihelmin, analgesic, hypotensive, anti-inflammatory, and immune enhancing effects. Photochemical analyses of ethanol and hexane extracts of noni fruit revealed the presence of flavonoids, terpenoids, alkaloids and steroids. Proximate composition of the noni fruit revealed a moisture content of 54.21, crude protein 2.18, crude fat 3.25, crude fiber 4.49, ash 0.73 and carbohydrate 35.14%. The Vitamin C content was estimated using iodometric titration and found to be 134.10 mg/100g. This suggests that the noni fruit can if consumed can help promote good health.